Deliberate Self-Harm in Substance Use Disorder Patients-A Study at Tertiary Level Hospitals in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Deliberate Self-harm is a term introduced to describe patients who injure themselves by self-mutilation (e.g. cutting the skin) but usually do not wish to die. Studies show that about 4 percent of all patients in psychiatric hospitals have cut themselves; the female-to-male ratio is almost 3 to 1. Self-injury is found in about 30 percent of all abusers of oral addiction substances and 10 percent of all intravenous drug users admitted to substance-treatment units. These patients are usually in their 20s and may be single or married. Most cut delicately, not coarsely, usually in private with a razor, blade, knife, broken glass or mirror. The wrists, arms, thighs and legs are most commonly cut; the face, breasts and abdomen are cut infrequently. Most persons who cut themselves claim to experience no pain and give reasons, such as anger at themselves or others, relief of tension and the wish to die. Methods: It was an explorative descriptive cross sectional study aimed to explore the pattern of deliberate self harm among substance use disorder patients in three selected hospital. The research design was Quantitative in nature. The study sites were Central Drug Addiction Treatment Centre, Dhaka; Combined Military Hospital, Dhaka Cantonment, Dhaka and Modern Psychiatric Hospital, Dhaka. The study population was Substance abusers seeking advice or getting treatment in Central Drug Addiction Treatment Centre, Dhaka; Combined Military Hospital, Dhaka Cantonment, Dhaka and Modern Psychiatric Hospital, Dhaka. Results: The mean age of onset of taking drugs was 24 to 42 years with the SD ± 6.83. The range was in between 12 and 57 years and adolescents were greatly involved in self harm. Many of them used more than one substance; among them 56% mentioned about Cannabis. Among all the respondents 52 of them reported that they use substances several times daily. Regarding the route of administration, among all the respondents, they have history of using multiple routes for administering the substances. 73% of them reported that they use substances by smoking. In this study it was revealed that, the substance users follow several methods for self harm. Among them, cutting, burning, scratching, stabbing etc are noteworthy. 39% of the substance users harmed themselves by cutting in the first episode which follows same trends in next episodes. Conclusion: Deliberate self harm is a behavior that over the time becomes compulsive and addictive. Finding out the causes of deliberate self harm among substance related disorders will help us choose an appropriate remedy of this non-fatal but repetitive and distressing behavior which may lead to completed suicide. Systematic mental health assessments in the emergency department of following an episode of deliberate self-harm may improve detection of mental disorders. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18728 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 63-74